The role of the satellite market in provisioning broadband access in Europe up to 2030 - Oliver Johnson; Arnold Kürsteiner (International Telecommunications Society (ITS), 2023)
Gigabit broadband, at least 1 Gbps bandwidth downstream, available to all is a key objective of the European Union and European states overall. The target has been part of the landscape in most areas for a number of years now. There are variations in exactly when and how this coverage objective is expected to be reached. Our modelling of the extent of the deployment of fixed networks and the resulting and inevitable gaps in that coverage result in between 33 and 71 million people (6.2% to 13.6% of total population)3 without access to gigabit-capable technologies, or 480 thousand to 1.7 million square kilometres4 of land where fixed rollout of 1Gbps-capable technologies will not be completed. In common with previous targets and outcomes we expect those gaps to be addressed in large part by satellite broadband services. Our modelling suggests a potential market size of between EUR 3.8 million and 8.1 million.
Keywords: 330